Stomach content analysis and length-weight relationship of the Pontic shad Alosaimmaculata Bennett, 1835 (Pisces: Clupeidae), from the eastern Black Seacoast of Turkey - Mazlum, Rahsan Evren; Akgumus, Sevkiye (Indian Journal of Fisheries, 2019)
Diet composition of the anadromous Pontic shad Alosa immaculata Bennett, 1835 was studied in relation to season and body size, from samples collected from the south-east Black Sea coast of Turkey in spring, autumn and winter during the period from March 2012 - February 2013. Out of 236 samples, 226 stomachs contained food and 24 prey items were identified. Nematoda sp. and teleosts were the main prey items with index of relative importance (IRI) of 59.3 and 38.2% respectively. Seasonal analysis showed that the IRI of Nematoda sp. was 71.6% in winter, 50.6% in spring and 37.1% in autumn. The stomachs of fishes in the length range of 12.0 -19.9 cm contained a higher proportion of Nematoda sp. (IRI up to 74 - 80%). Larger fishes in the length range of 24.0-32.8 cm consumed more teleosts (>45% IRI) than the others. The length-weight relationship showed that females grow in positive allometric pattern while males have isometric growth.